Convergent evolution of oxidized sugar metabolism in commensal and pathogenic microbes in the inflamed gut - Sophia Levy; Angela K. Jiang; Maggie R. Grant; Gabriela Arp; Glory Minabou Ndjite; Xiaofang Jiang; Brantley Hall (Nature Communications)
Abstract Inflammation-associated perturbations of the gut microbiome are well characterized, but poorly understood. Here, we demonstrate that disparate taxa recapitulate the metabolism of the oxidized sugars glucarate and galactarate, utilizing enzymatically divergent, yet functionally equivalent, gud/gar pathways. The divergent pathway in commensals includes a putative 5-KDG aldolase (GudL) and an uncharacterized ABC transporter (GarABC) that recapitulate the function of their non-homologous counterparts in pathogens. A systematic bioinformatic search for the gud/gar pathway in gut microbes identified 887 species putatively capable of metabolizing oxidized sugars. Previous studies showed that inflammation-derived nitrate, formed by nitric oxide reacting with superoxide, promotes pathogen growth. Our findings reveal a parallel phenomenon: oxidized sugars, also produced from reactions with nitric oxide, serve as alternative carbon sources for commensal microbes. Previously considered a pathogen virulence factor, oxidized sugar metabolism is also present in specific commensals and may contribute to their increased relative abundance in gastrointestinal inflammation.